Improving function of older people receiving a restorative care service - Burton, Elissa; Lewin, Gill; Clemson, L; Boldy, Duncan (Blackwell Publishing, 2012)
To help maintain strength, balance and endurance and to decrease the chances of falling, it is important for older people to remain physically active. Restorative home care services are available to older people when they have an injury or illness or require some assistance to continue living independently. These services are short-term and have multiple components, including a physical activity program, and they are often delivered by allied health professionals. The aim of this study was to assess the effectiveness of two different physical activity programs delivered as part of a restorative service (the exercise program currently delivered versus LiFE, a lifestyle activity program developed by Clemson et al at the University of Sydney) in improving the strength and balance of service recipients. The study was designed as a randomized controlled trial in which functioning at baseline was compared to post-intervention functioning eight weeks later. When recruited, all participants were already receiving a Silver Chain restorative home care service, were aged over 65 years and had been assessed as needing an activity program by their Care Manager. Outcomes examined included: falls, balance, lower body strength, function and disability. Seventy-seven older people have participated in the study. Data collection will be complete by July 2012 and comparative effective analyses in September. The complete results will be presented and discussed in terms of how they add to the current evidence base as to the effectiveness of different types of exercise programs for older adults and how this knowledge may assist us to ensure that older people optimize their ability to stay living independently by improving/maintaining their strength and balance.